Bacillus anthracis Poly-γ-D-Glutamate Capsule Inhibits Opsonic Phagocytosis by Impeding Complement Activation - Sharma, Shikhar; Bhatnagar, Rakesh; Gaur, Deepak (Frontiers in Immunology, 2020)
Bacillus anthracis poly-γ-D-glutamic acid (PGA) capsule is an essential virulent factor that helps the bacterial pathogen to escape host immunity. Like other encapsulated bacterial species, the B. anthracis capsule may also inhibit complement-mediated clearance and ensure bacterial survival in the host. Previous reports suggest that B. anthracis spore proteins inhibit complement activation. However, the mechanism through which the B. anthracis capsule imparts a survival advantage to the active bacteria has not been demonstrated till date. Thus, to evaluate the role of the PGA capsule in evading host immunity, we have undertaken the present head-to-head comparative study of the phagocytosis and complement activation of non-encapsulated and encapsulated B. anthracis strains. The encapsulated virulent strain exhibited resistance toward complement-dependent and complement-independent bacterial phagocytosis by human macrophages. The non-encapsulated Sterne strain was highly susceptible to phagocytosis by THP-1 macrophages, after incubation with normal human serum (NHS), heat-inactivated serum, and serum-free media, thus indicating that the capsule inhibited both complement-dependent and complement-independent opsonic phagocytosis. An increased binding of C3b and its subsequent activation to C3c and C3dg, which functionally act as potent opsonins, were observed with the non-encapsulated Sterne strain compared with the encapsulated strain. Other known mediators of complement fixation, IgG, C-reactive protein (CRP), and serum amyloid P component (SAP), also bound more prominently with the non-encapsulated Sterne strain. Studies with complement pathway-specific, component-deficient serum demonstrated that the classical pathway was primarily involved in mediating C3b binding on the non-encapsulated bacteria. Both strains equally bound the complement regulatory proteins C4BP and factor H. Importantly, we demonstrated that the negative charge of the PGA capsule was responsible for the differential binding of the complement proteins between the non-encapsulated and encapsulated strains. At lower pH closer to the isoelectric point of PGA, the neutralization of the negative charge was associated with an increased binding of C3b and IgG with the encapsulated B. anthracis strain. Overall, our data have demonstrated that the B. anthracis capsule inhibits complement fixation and opsonization resulting in reduced phagocytosis by macrophages, thus allowing the bacterial pathogen to evade host immunity.